2013
DOI: 10.1111/jpm.12112
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, social support, and severity of psychiatric symptoms in Jordanian patients with schizophrenia

Abstract: The major purposes of this study were to examine levels and correlations of quality of life (QOL), social support, and severity of psychiatric symptoms as well as to identify the variables that best predict QOL among Jordanian patients with schizophrenia. Descriptive cross-sectional design was used to collect data from 160 patients selected through systematic random sampling from two psychiatric outpatient clinics. Results showed that the highest domain of QOL was the social relationship domain, and the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 37 publications
5
31
0
1
Order By: Relevance
“…In our research, the explanation of multi-level predicators and HRQOL of patients with depression or schizophrenia is just range from six to thirty six percent. The similar results also can be found in other previous researches [26,27].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our research, the explanation of multi-level predicators and HRQOL of patients with depression or schizophrenia is just range from six to thirty six percent. The similar results also can be found in other previous researches [26,27].…”
Section: Discussionsupporting
confidence: 91%
“…And more interestingly, the socio-demographic of ethnicity and medical factor of degree of disease have opposite impact functions on the HRQOL between these two patient groups. An interesting result is also found that the more severe the degree of schizophrenia is in onset, the higher score of HRQOL is, this result is similar with some result in China, however, it seems to be opposite conclusion with the study of Hamaideh S, which show that it is correlated positively with patients education, negatively with severity of psychiatric symptoms [27]. It also indicate that there may be some heterogeneous reasons in same factor we are not determined.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Por tanto, es crucial la implementación de las intervenciones de enfermería en salud mental que promueven relaciones interpersonales no sólo dentro del grupo terapéutico, sino también en la comunidad. DESCRIPTORES: Esquizofrenia; Apoyo social; Calidad de Vida Submetido em 27-01-2017 Aceite em 20-06-2017 Existem já alguns estudos, que evidenciam que quanto maior o apoio social dos doentes com esquizofrenia, melhor a qualidade de vida (Hamaideh, Al-Magaireh, Abu-Farsakh, & Al-Omari, 2014;Lanfredi et al, 2014;Suttajit, & Pilakanta, 2015). Outros, relacionam a perceção de apoio social destes doentes com esta mesma variável (Adelufosi, Ogunwale, Abayomi, & Mosanya, 2013;Eack, Newhill, Anderson, & Rotondi, 2007;Gutiérrez-Maldonado et al, 2012).…”
Section: Introductionunclassified
“…[6][7][8]). In both the general population, and for people with various mental health challenges, social support has been considered to be related to quality of life [9][10][11][12][13][14][15][16][17][18][19], and recovery [20,21].…”
Section: Introductionmentioning
confidence: 99%